2015
DOI: 10.1093/jxb/erv499
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and physiological analyses reveal co-ordinated alteration of metabolic pathways inJatropha curcasdrought tolerance

Abstract: Jatropha curcas, a multipurpose plant attracting a great deal of attention due to its high oil content and quality for biofuel, is recognized as a drought-tolerant species. However, this drought tolerance is still poorly characterized. This study aims to contribute to uncover the molecular background of this tolerance, using a combined approach of transcriptional profiling and morphophysiological characterization during a period of water-withholding (49 d) followed by rewatering (7 d). Morphophysiological meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…In the present study, we combined transcriptomics with morphophysiology to investigate further the molecular mechanisms underlying the improved photosynthesis under elevated CO 2 in Jatropha . The library preparation in our study was significantly good as demonstrated by the assembly statistics in which N50 value, average contig length, total number of contigs, longest contig length and number of assembled unigenes were higher in both sample A and E libraries in comparison to similar studies on Jatropha transcriptome under different conditions 21 , 25 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the present study, we combined transcriptomics with morphophysiology to investigate further the molecular mechanisms underlying the improved photosynthesis under elevated CO 2 in Jatropha . The library preparation in our study was significantly good as demonstrated by the assembly statistics in which N50 value, average contig length, total number of contigs, longest contig length and number of assembled unigenes were higher in both sample A and E libraries in comparison to similar studies on Jatropha transcriptome under different conditions 21 , 25 .…”
Section: Discussionsupporting
confidence: 55%
“…However, studies on transcriptome analysis of Jatropha were limited to regulatory aspects of oil biosynthesis in developing seeds with little emphasis on growth and photosynthesis 17 , 18 . Furthermore, few transcriptome studies, reported for growth of Jatropha under different environmental conditions, were limited to seedlings or pot-grown plants with no reports on plants grown for longer durations in field conditions 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enhanced ROS scavenging capacity in response to abiotic stresses may be a common effect of polyploidization that directly contributes to enhanced stress tolerance. Soluble sugars, especially sucrose, glucose and fructose, function not only as an energy source but also as osmoprotectants in plants, indicating that they play an important role in various physiological and biological processes, including growth, development and stress response (Cou ee et al, 2006;Ruan, 2014;Sapeta et al, 2016). Sucrose is irreversibly hydrolysed by invertase (INV) into glucose and fructose (Roitsch and Gonz alez, 2004;Ruan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of low-cost next generation sequencing (NGS) technologies, transcriptome analysis through NGS has become a fast and powerful approach for genome-wide gene discovery and molecular marker development [1921]. Transcriptomics has been used in jatropha to study gene expression profiles related to cold stress [22]; gene expression in seeds [23]; oil metabolism in maturing seeds [24]; impact of cytokinin on inflorescence buds [25]; metabolic pathways in drought tolerance [26]; and apical meristem [27]. Availability of these resources helps in jatropha gene discovery and crop improvement using molecular tools.…”
Section: Introductionmentioning
confidence: 99%